2014
DOI: 10.1111/ans.12713
|View full text |Cite
|
Sign up to set email alerts
|

130‐ versus 135‐degree sliding hip screws and failure in pertrochanteric hip fractures

Abstract: We believe the improved trajectory for lag screw placement using 130-degree angled plates leads to a lower TAD and improved fixation in pertrochanteric fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The well-known concept of the sliding hip screw was first popularized by Schumpelick et al [ 13 ] in 1955 as a fixed-angle device with variable length. The sliding barrel is designed to provide compression through a tension band mechanism and transmit the forces through the medial cortex of the proximal femur [ 14 ]. Controlled fracture impaction and union are more reliably achieved when the lag screw is positioned in the subchondral bone, and progressive load sharing with the bone is maintained; this is usually accomplished when the lag screw is perpendicular to the fracture line of the femoral neck [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-known concept of the sliding hip screw was first popularized by Schumpelick et al [ 13 ] in 1955 as a fixed-angle device with variable length. The sliding barrel is designed to provide compression through a tension band mechanism and transmit the forces through the medial cortex of the proximal femur [ 14 ]. Controlled fracture impaction and union are more reliably achieved when the lag screw is positioned in the subchondral bone, and progressive load sharing with the bone is maintained; this is usually accomplished when the lag screw is perpendicular to the fracture line of the femoral neck [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study confirmed that using a lower angle (125° or 130°) implant allows for better positioning of the lag screw and, consequently, better TAD and less chance of cutout. Radic et al [ 14 ] suggested that a 130° angle more closely matches “normal” proximal femoral anatomy and would allow for a more straightforward trajectory for screw placement to achieve the desired TAD of 25 mm or less. They compared 130° DHS plates versus 135° DHS plates, and their study showed a statistically significant difference in TAD between them.…”
Section: Discussionmentioning
confidence: 99%
“…The 250,000 proximal femoral fractures reported per year in the US are projected to increase to 500,000 by the year 2040 [2]. Intertrochanteric hip fractures, which are particularly deadly and expensive, account for as much as 50% of all proximal femoral fractures [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…DHS failure rates as high as 16-23% have been reported [1,2]. The most common form of failure is screw cut-out, in which the neck-shaft angle collapses into varus, causing the screw to penetrate the femoral head and possibly enter the joint space [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%